2005
DOI: 10.1016/j.gca.2004.10.017
|View full text |Cite
|
Sign up to set email alerts
|

The effect of phytostabilization on Zn speciation in a dredged contaminated sediment using scanning electron microscopy, X-ray fluorescence, EXAFS spectroscopy, and principal components analysis

Abstract: Running Title: Effect of phytostabilzation on Zn speciation in dredged sediment 2 ABSTRACTThe maintenance of waterways generates large amounts of dredged sediments, which are deposited on adjacent land surfaces. These sediments are often rich in metal contaminants and present a risk to the local environment. Understanding how the metals are immobilized at the molecular level is critical for formulating effective metal containment strategies, such as phytoremediation. In the present work, the mineralogical tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
129
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(143 citation statements)
references
References 109 publications
12
129
2
Order By: Relevance
“…This result was consistent with the identification of pyrite (FeS) and sphalerite (ZnS) in similar sediments (ISAURE et al, 2002;PANFILI et al, 2005). CdS was also identified in marine sediments (O'DAY et al, 1998).…”
Section: Is Phytoextraction a Suitable Green Treatment For Metal Contsupporting
confidence: 87%
See 2 more Smart Citations
“…This result was consistent with the identification of pyrite (FeS) and sphalerite (ZnS) in similar sediments (ISAURE et al, 2002;PANFILI et al, 2005). CdS was also identified in marine sediments (O'DAY et al, 1998).…”
Section: Is Phytoextraction a Suitable Green Treatment For Metal Contsupporting
confidence: 87%
“…The sediment after 5-month culture with A. halleri is currently being studied. PANFILI et al (2005) showed that plants favour the oxidation of ZnS and the formation of Zn-phosphate, so a similar phenomenon might take place for Cd. Open questions include the stability of the Cd,Zn,Fe-sulphide and the nature of the distribution of possible secondary species.…”
Section: Figure 3 (A) Backscattered Electron Sem Image (B) Eds Specmentioning
confidence: 83%
See 1 more Smart Citation
“…If the measured total trace elements concentrations correspond only (or mainly) to these dangerous substances, a hypothesis maximizing the potential hazard, the linear correlations between the concentrations (mg/kg) of pairs of trace elements should be highly significant (0.01 level) with a slope of the correlation (or median ratio of concentrations) equal (or very close) to the ratio of atomic mass of the two elements considered, i. e.1.26 for the correlation Zn/Cr, 0.8 for Cr/Zn, 2.77 for Pb/As, 0.36 for As/Pb, 3.99 for Pb/Cr, and 0.25 for the correlation Cr/Pb. Such an indirect estimation of the possible presence of dangerous inorganic substances is made necessary by the fact that neither chemical techniques for operationally-defined speciation of metals (Tessier et al 1979), nor more specific spectroscopic techniques (O'Day et al 2000;Panfili et al 2005;Peltier et al 2005) enable the identification of specific substances.…”
Section: Data Sets Available and Statistical Analysismentioning
confidence: 99%
“…X-ray fluorescence, scanning electron microscopy, extended x-ray absorption fine structure spectroscopy and principal component analysis were applied to the evaluation of the effect of phytostabilization on Zn speciation in a dredged contaminated sediment. 104 Kohonen artificial neural network was applied to classify energy dispersive x-ray spectra of 12 mineralogical samples. By extracting 12 rules and seven element intensities out of 15, 100% correct classification of samples was obtained.…”
Section: Applications Of Pattern Recognition Approaches To Xrsmentioning
confidence: 99%